Ars Non Scribendi as Artwork of the Absent: The Art of Not Writing in Ivan Vladislavić's The Loss Library. Issue 2 (2nd July 2016) - Swanepoel, Rilette
Abstract : In The Loss Library and Other Unfinished Stories (2011), Ivan Vladislavić takes his characteristic genre experimentation to a new extreme. Presenting story ideas, bits of research and anecdotes, he interrogates several literary genres, but the volume as a whole has few obvious generic antecedents. Here I briefly consider the established literary genres that the author explores, and argue that the text is closer to a type of fine arts and artefacts that has always fascinated Vladislavić: those that commemorate loss. To refer to what he does in The Loss Library, I coin the term ars non scribendi – the art of not writing – as the inverse of ars poetica, the closest genre to (almost) accommodate the text. Encouraged by Vladislavić calling Micha Ullman an artist of the absent, I call the genre of The Loss Library and these other works 'art of the absent'. Aligning Vladislavić's ars non scribendi with artworks that he has written about in non-fiction or invented in his fiction, I show that the book represents and mourns loss, and conclude that The Loss Library 's genre-transcendence gives form to loss and absence.